Wildlife and warfare: a case study of pachyderms in Garamba National Park, DRC - Kes Smith (Pachyderm)
Wildlife conservation planning, funding and implementation often takes account of and sets priorities on the basis of wildlife numbers, biodiversity and species habitat, protected area status and their value in the bigger landscape picture, practicality and the chances of success—which reflect well on the funding body. Armed conflict is almost always seen as a negative factor and in the case of it arising, many organisations pull out. The Democratic Republic of Congo has been affected by several such conflicts but has also benefitted from the first project aimed specifically at maintaining biodiversity conservation during armed conflict. This paper takes Garamba National Park, DRC as a case study, presents population data of the main large mammals from 40 years of systematic aerial survey and relates trends to the specific effects of eight conflict crises and times of peace and the presence or absence of international support between 1960 and 2016. It draws lessons learned from first hand experience of the mechanisms and secondary effects of armed conflict and the approaches to maintaining conservation during such periods.